High‐Entropy Metal–Organic Frameworks and Their Derivatives: Advances in Design, Synthesis, and Applications for Catalysis and Energy Storage - Jiangyuan Xing; Yan Liu; George Mathew; Qiu He; Jasmin Aghassi‐Hagmann; Simon Schweidler; Ben Breitung (Advanced Science)
Abstract As a nascent class of high‐entropy materials (HEMs), high‐entropy metal–organic frameworks (HE‐MOFs) have garnered significant attention in the fields of catalysis and renewable energy technology owing to their intriguing features, including abundant active sites, stable framework structure, and adjustable chemical properties. This review offers a comprehensive summary of the latest developments in HE‐MOFs, focusing on functional design, synthesis strategies, and practical applications. This work begins by presenting the design principles for the synthesis strategies of HE‐MOFs, along with a detailed description of commonly employed methods based on existing reports. Subsequently, an elaborate discussion of recent advancements achieved by HE‐MOFs in diverse catalytic systems and energy storage technologies is provided. Benefiting from the application of the high‐entropy strategy, HE‐MOFs, and their derivatives demonstrate exceptional catalytic activity and impressive electrochemical energy storage performance. Finally, this review identifies the prevailing challenges in current HE‐MOFs research and proposes corresponding solutions to provide valuable guidance for the future design of advanced HE‐MOFs with desired properties.